Increased hepcidin levels in high-altitude pulmonary edema - Altamura, Sandro; Bärtsch, Peter; Dehnert, Christoph; Muckenthaler, Martina; Mairbäurl, Heimo (Journal of applied physiology, 2015)
Low iron availability enhances hypoxic pulmonary vasoconstriction (HPV). Considering that reduced serum iron is caused by increased erythropoiesis, insufficient reabsorption, or elevated hepcidin levels, one might speculate that exaggerated HPV in high-altitude pulmonary edema (HAPE) is related to low serum iron. To test this notion we measured serum iron and hepcidin in blood samples obtained in previously published studies at low altitude and during 2 days at 4,559 m (HA1, HA2) from controls, individuals with HAPE, and HAPE-susceptible individuals where prophylactic dexamethasone and tadalafil prevented HAPE. As reported, at 4,559 m pulmonary arterial pressure was increased in healthy volunteers but reached higher levels in HAPE. Serum iron levels were reduced in all groups at HA2. Hepcidin levels were reduced in all groups at HA1 and HA2 except in HAPE, where hepcidin was decreased at HA1 but unexpectedly high at HA2. Elevated hepcidin in HAPE correlated with increased IL-6 at HA2, suggesting that an inflammatory response related to HAPE contributes to increased hepcidin. Likewise, platelet-derived growth factor, a regulator of hepcidin, was increased at HA1 and HA2 in controls but not in HAPE, suggesting that hypoxia-controlled factors that regulate serum iron are inappropriately expressed in HAPE. In summary, we found that HAPE is associated with inappropriate expression of hepcidin without inducing expected changes in serum iron within 2 days at HA, likely due to too short time. Although hepcidin expression is uncoupled from serum iron availability and hypoxia in individuals developing HAPE, our findings indicate that serum iron is not related with exaggerated HPV.